Relationship between the Na+/H+ antiporter and Na+/substrate symport in Bacillus alcalophilus. - Guffanti, A A (1981)
The Na+/H+ antiporter of the obligate alkalophile Bacillus alcalophilus facilitates growth at alkaline pH and precludes growth below pH 8.5. Thus, nonalkalophilic mutant strains do not exhibit Na+/H+ antiport activity and, interestingly, such strains concomitantly lose the ability to catalyze Na+-dependent accumulation of alpha-aminoisobutyrate [Krulwich, T. A., Mandel, D. G. Bornstein, R. F. & Guffanti, A. A. (1979) Biochem. Biophys. Res. Commun. 91, 58-62]. Several other Na+-dependent transport systems are now documented in vesicles from the wild-type strain, and it is demonstrated that these systems are defective in vesicles from the nonalkalophilic mutant KM23. Surprisingly, the defect seems to result not from the loss of Na+/H+ antiport activity per se but from a pleiotropic defect in the Na+/substrate symporters themselves. Monensin, an ionophore that catalyzes Na+/H+ exchange, does not restore respiration-driven Na+/substrate symport in KM23 vesicles. Moreover, with KM23 vesicles, efflux of alpha-aminoisobutyrate, L-malate, and L-aspartate down their respective concentration gradients is not stimulated by Na+, in contrast to the observations with wild-type vesicles. Because monensin should ameliorate a simple defect in Na+/H+ antiport activity and the antiporter should not be required for Na+/substrate symport down a concentration gradient, the results suggest that there may be a direct relationship between the antiporter and various Na+/substrate symporters. One possibility is that the systems share a Na+-translocating subunit.